The Multifaceted B Cell Response to Influenza Virus - Lam, Jonathan H. (J Immunol, 2019)
Protection from yearly recurring, highly acute infections with a pathogen that rapidly and continuously evades previously induced protective neutralizing antibodies, as seen during seasonal influenza virus infections, can be expected to require a B cell response that too is highly variable, able to adapt rapidly and to reduce morbidity and death when sterile immunity cannot be garnered quickly enough. As we outline in this brief review, the influenza-specific B cell response is exactly that: It is multifaceted, involves both innate-like and conventional B cells, provides early and later immune protection, employs B cells with distinct BCR repertoires and distinct modes of activation, and continuously adapts to the ever-changing virus while enhancing overall protection. A formidable response to a formidable pathogen.